Analysis of deflection in visco-thermoelastic beam resonators subjected to harmonic loading - Chopra, Deepti; Singh, Prince (Zielona Góra: Uniwersytet Zielonogórski)
This paper analyses the transverse deflection in a homogeneous, isotropic, visco-thermoelastic beam when subjected to harmonic load. The ends of the beam are considered at different boundary conditions (both axial ends clamped, both axial ends simply supported and left end clamped and right end free).
Keywords: visco-thermoelastic; beam; loading; Laplace